Pengaruh Penyuluhan Kesehatan Terhadap Pengetahuan Remaja Puteri Kelas VII Tentang Pubertas Di Pondok Pesantren Darul Hijrah Puteri Cindai Alus Martapura Kabupaten Banjar Tahun 2016 - Ermas Estiyana; Dianita Anggraini; Mutia Zairina (Jurnal Kesehatan Indonesia, 2017)
Adolescence is a time of transition in the span of human life. Commencement of adolescence is marked by puberty. In adolescence there is a change not only in the sense of psychological but also physical changes. In the implementation of International on Population and Development (ICPD) in Cairo in 1994, which says that the State shall protect and promote the rights of adolescents to education, information and reproductive health services and reduce the number of pregnancies teenagers so as to encourage the government and NGOs to develop programs that are responsive to adolescent sexual and reproductive issues. on a preliminary study of 10 respondents to the interview that only (40%) young women who answered true regarding the definition of puberty and (60%) were more answered wrong, the young women who answered correctly on when the age of the onset of puberty (60%) and (40 %) were the other answered incorrectly, young women who answered correctly on the characteristics of puberty only (30%) and (70%) were the other answered incorrectly. The research objective to analyze the effect of health education to young women about puberty. The method used was Quation Experimental. The subjects were students of class VII as many as 80 people were taken by random sampling technique. Results obtained 75 votes (95%) good knowledge and 4 (5%) sufficient knowledge. It was concluded that value p = 0,000 <α (0.05), which means that there are differences in knowledge young women about puberty. It is suggested to educational institutions in order to meet the information needs of health knowledge that is appropriate to be able to equip students become mature children who are ready physically and psychologically.